1980
DOI: 10.1128/aac.18.1.190
|View full text |Cite
|
Sign up to set email alerts
|

In vitro susceptibility testing of Paracoccidioides brasiliensis to sulfonamides

Abstract: A total of 60 clinical isolates of Paracoccidioides brasiliensis were tested for susceptibility to sulfadiazine and sulfadimethoxyne by the agar dilution technique. A modification of the Mueller-Hinton medium was devised which gave good growth of the yeast form. The minimum inhibitory concentrations for only 51.6% of the isolates were in the range of the recommended blood serum concentration (50 ,ug/ml (7,14).In spite of these observations, there has been no survey of the in vitro susceptibility of the causat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 8 publications
(10 reference statements)
1
20
0
2
Order By: Relevance
“…16) Moreover, it has been reported that the combination of SMX and TMP acts synergistically against the dimorphic fungus Paracoccidioides brasiliensis. 17,18) Those reports suggest that SMX-TMP acts toward fungus. In the present study ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…16) Moreover, it has been reported that the combination of SMX and TMP acts synergistically against the dimorphic fungus Paracoccidioides brasiliensis. 17,18) Those reports suggest that SMX-TMP acts toward fungus. In the present study ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is inexpensive, may be infused intravenously in the severe forms of PCM, it is easy to administer orally and it is available in public health services. According to some, failures of treatment with this association are mostly secondary to poor patient compliance 19,24,27,30 .…”
Section: Radiologymentioning
confidence: 99%
“…MMH medium is not a chemically defined medium, and microorganisms can obtain folic acid or its precursors from different sources. MMH medium was tested in our study because it was previously used in MIC assays with agar dilution for P. brasiliensis isolates (23), yielding values similar to those obtained in RPMI 1640 medium, and because yeast morphology was maintained at 37°C in this medium until the end of the protocol. Our results showed that the MICs with MMH medium were similar to those found with RPMI 1640 medium when sulfamethoxazole and the sulfamethoxazole-trimethoprim combination were tested.…”
Section: Discussionmentioning
confidence: 99%
“…The standard RPMI 1640 medium at 34.54 g per liter was buffered with 0.165 M morpholinepropanesulfonic acid (MOPS) at pH 7.0. MVM medium was prepared as recommended by Restrepo and Jimé-nez (30), and MMH medium (Mueller-Hinton medium supplemented with 10 g/liter of glucose, 5 g/liter of ammonium sulfate, and 10 mg/liter of thiamine [Sigma-Aldrich]) was prepared as recommended by Restrepo and Arango (23). All drugs were tested in these three media for all of the isolates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation